1991
DOI: 10.1093/carcin/12.5.793
|View full text |Cite
|
Sign up to set email alerts
|

Study of the separate and combined effects of the non-planer 2,5,2′,5′-and the planner 3,4,3′,4′-tetrachlorobiphenyl in liver and lymphocytes in vivo

Abstract: Polychlorinated biphenyls (PCBs) are a group of industrial chemicals that are widely distributed in the environment. Because these compounds occur as mixtures, studies of their possible interactive effects are essential for an understanding of the mechanism of the toxicity of these mixtures. For the determination of a possible interaction of the effects in vivo of 2,5,2',5'-tetrachlorobiphenyl (TCB) and 3,4,3',4'-TCB, rats were exposed to a single dose of diethylnitrosamine (DEN) and subsequently to 0.1 p.p.m.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 0 publications
3
17
0
2
Order By: Relevance
“…The macroscopic lesions and tumors found after 52 weeks of treatment give further support to this conclusion. These results are in agreement with other studies in which both coplanar and nonplanar PCBs have been shown to act as tumor promoters by enhancing the development of preneoplastic lesions and tumors in rats and mice after treatment with various mutagens Buchmann et ai, 1991;Sargent et al, 1991;Hemming et al, 1993).…”
Section: Discussionsupporting
confidence: 93%
“…The macroscopic lesions and tumors found after 52 weeks of treatment give further support to this conclusion. These results are in agreement with other studies in which both coplanar and nonplanar PCBs have been shown to act as tumor promoters by enhancing the development of preneoplastic lesions and tumors in rats and mice after treatment with various mutagens Buchmann et ai, 1991;Sargent et al, 1991;Hemming et al, 1993).…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that this route of PCB metabolism could form semi-quinone radicals which could mediate cytotoxicity by leading to increased intracellular steady-state levels of O 2 ·− and H 2 O 2 [39]. Since ROS are known to play a role in both mitogenesis and genomic instability [12], which may contribute to carcinogenesis, it has been proposed that PCB-induced metabolic oxidative stress contributes to neoplastic transformation [7, 8, 40, 41] and other deleterious effects of PCBs and their metabolites [5, 7, 8, 14]. However, despite the interest in PCB-induced oxidative stress there is very little direct evidence in living cells identifying the specific ROS involved in mediating PCB induced cell injury or identifying the intracellular sites of ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…PCB 52 was shown to induce DNA damage in cultured human lymphocytes (Sandal et al , 2008) and to induce and promote tumors in rat liver (Espandiari et al, 2003; Preston et al, 1985). Highly interesting is that PCB 52 acted synergistically with PCB 77 with respect to genotoxic and cancer initiating activity (Meisner et al, 1992; Sargent et al, 1991; Sargent et al, 1989). It should be considered, however, that these experiments were done with single/few/short term exposures to high doses/concentrations, a completely different scenario than our daily long term low dose exposure through air and food.…”
Section: Introductionmentioning
confidence: 99%